2019
DOI: 10.1016/j.molcel.2019.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PARP-1 by snoRNAs Controls Ribosome Biogenesis and Cell Growth via the RNA Helicase DDX21

Abstract: PARP inhibitors (PARPi) prevent cancer cell growth by inducing synthetic lethality with DNA repair defects (e.g., in BRCA1/2 mutant cells). We have identified an alternative pathway for PARPi-mediated growth control in BRCA1/2-intact breast cancer cells involving rDNA transcription and ribosome biogenesis. PARP-1 binds to snoRNAs, which stimulate PARP-1 catalytic activity in the nucleolus independent of DNA damage. Activated PARP-1 ADP-ribosylates DDX21, an RNA helicase that localizes to nucleoli and promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
196
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(208 citation statements)
references
References 65 publications
12
196
0
Order By: Relevance
“…48,49 Therefore, we inferred that USP34 or SNORA70B might bind WNT pathway-related protein to activate it. 48,49 Therefore, we inferred that USP34 or SNORA70B might bind WNT pathway-related protein to activate it.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…48,49 Therefore, we inferred that USP34 or SNORA70B might bind WNT pathway-related protein to activate it. 48,49 Therefore, we inferred that USP34 or SNORA70B might bind WNT pathway-related protein to activate it.…”
Section: Discussionmentioning
confidence: 97%
“…Lasted studies have reported that snoRNAs could directly bind to functional protein to promote tumorigenesis. 48,49 Therefore, we inferred that USP34 or SNORA70B might bind WNT pathway-related protein to activate it.…”
Section: Discussionmentioning
confidence: 97%
“…PARP inhibitors are also effective in Ewing's sarcomas by blocking, on the one hand, PARP1-dependent transcriptional activation effects of ETS gene fusions such as EWS-FLI-1, and by exacerbating DNA damage on the other (Brenner et al 2012). Furthermore, PARP inhibitors reduce rDNA transcription and ribosome biogenesis in BRCA1/2-proficient cancer cells by preventing DDX21 ADP-ribosylation, and thereby reduce breast cancer growth (Kim et al 2019).…”
Section: Targeting Transcription Rna Metabolism and Ribosome Biogenmentioning
confidence: 99%
“…ASO-mediated knockdown of SNORA74A engendered a substantial decrease in DDX21 ADPRylation and cell proliferation, confirming that snoRNAs can activate PARP-1 in the absence of DNA damage. It was also shown that DDX21 can bind snoRNAs such as SCARNA2 on its C-terminal RNA-binding domain [74]. These snoRNAs were suggested to compete with the PARP-1 and DDX21 interactions.…”
Section: Binding Competition Protein Activation and Protein Trappingmentioning
confidence: 99%
“…The inhibition of PARP-1 is helpful in the treatment of cancers because it causes accumulation of DNA damage and synthetic lethality of cancer cells presenting defects in homologous recombination (HR)-mediated DNA repair machinery [72]. However, even tumors with non-mutated HR machinery were recently shown to be affected by PARP inhibitors [73], and Kim et al [74] discovered a mechanism that can explain this. Indeed, several mature H/ACA box snoRNAs (notably SNORA73A, SNORA73B and SNORA74A) can bind to PARP-1, leading to the activation of its ADPRylation (PAR) function.…”
Section: Binding Competition Protein Activation and Protein Trappingmentioning
confidence: 99%